E‐Skin: E‐Skin Tactile Sensor Matrix Pixelated by Position‐Registered Conductive Microparticles Creating Pressure‐Sensitive Selectors (Adv. Funct. Mater. 31/2018). (30th July 2018) - You, Insang; Choi, Song‐Ee; Hwang, Hyejin; Han, Sang Woo; Kim, Jin Woong; Jeong, Unyong
Abstract : A high‐resolution E‐skin matrix without electrical crosstalk between the pixels is manufactured by Jin Woong Kim, Unyong Jeong, and co‐workers in article number1801858 . The diode‐based tactile sensor matrix uses a position‐registered conductive microparticles array and its Schottky junctions with a flexible hybrid electrode. This new, transistor‐free approach to E‐skin offers a flexible electronic balance and can finger read Braille.